The Role of Human Capital and Innovation in Prussian Economic Development - Francesco Cinnirella; Jochen Streb (Center for Economic Studies and ifo Institute (CESifo), 2013)
By merging individual data on valuable patents granted in Prussia in the late nineteenth century with county level information on literacy and income tax revenues we show that increases in the stock of human capital not only improved workers' productivity but also accelerated innovative activities which, in turn, evoked an additional rise in the productivity level. Instrumenting the stock of literate people with information on the number of blind and deaf-mute people we also establish the direct causal effect of human capital on income, net of the innovation channel.
Keywords: N13; N33; O11; O31; 330; human capital; growth; literacy; innovation; patents; Prussia